CFD Analysis of Airflow around A F1 Race Car to Test Aerodynamics - Lenin Rakesh, N.; Teja, Prabhu; Sandeep, M.; Madini Babu, M.; Sai Pavan, M. (International Journal of Psychosocial Rehabilitation, 2019)
The sport of Formula 1 (F1) has been a proving ground for race fanatics and engineers for more than half a century. With every driver wanting to go faster and beat the previous best time, research and innovation in the engineering of the car are really essential. Although higher speeds are the main criterion for determining the Formula 1 car’s aerodynamic setup, post the San Marino Grand Prix of 1994, the engineering research and development has also targeted driver’s safety. The governing body of Formula 1, i.e., Fédération Internationale de l’Automobile (FIA), has made significant rule changes since this time, primarily targeting car safety and speed. Aerodynamic performance of a F1 car is currently one of the vital aspects of performance gain, as marginal gains are obtained due to engine and mechanical changes to the car. Thus, it has become the key to success in this sport, resulting in teams spending millions of dollars on research and development in this sector each year. Although F1 car aerodynamics is at a highly advanced stage, there is always potential for further development.